Highly stable and water-soluble monodisperse CsPbX3/SiO2 nanocomposites for white-LED and cells imaging. (14th June 2018) - Ding, Nan; Zhou, Donglei; Sun, Xuke; Xu, Wen; Xu, Hongwei; Pan, Gencai; Li, Dongyu; Zhang, Shuang; Dong, Biao; Song, Hongwei
Abstract: In spite of the excellent optical properties of all-inorganic halide perovskite quantum dots (PQDs), they still suffer from inherent poor stability even when exposed to moisture from the atmosphere, restricting their applications, especially in white-light-emitting diodes (LEDs) and cells imaging. Here, we proposed a strategy by encapsulating the CsPbX3 (X = Cl, Br, I) PQDs into silica nanoplates to prepare highly stable and water-soluble CsPbX3 /SiO2 nanocomposites. First, the 120 nm monodisperse CsPbX3 /SiO2 nanocomposites inlayed with several CsPbX3 PQDs were fabricated via the modified Stöber method. After coating, their stability exposed in the air was largely improved for all the CsPbX3 (X = Cl, Br, I) PQDs without changing their emission peaks and full-width at half-maximum, attributed to the suppression of the anion-exchange and decomposition. Moreover, further experiments demonstrated that the CsPbX3 /SiO2 nanocomposites were highly water-soluble and stable in the water. Their applications in LEDs and cell imaging demonstrated their ultrastability and high biocompatibility. Therefore, this study shows the possibility of their use in photoelectric devices and biological applications.